Barron's American Sign Language : a comprehensive guide to ASL 1 and 2 - Stewart, David A. (David Alan), 1954-2004; Stewart, Jennifer, M.S. Ed (Kaplan North America, LLC d/b/a Barron's Educational Series, 2021)
Presents a guide to learning sign language, including fingerspelling, illustrated signs, quizzes, and more.